2016
DOI: 10.1016/j.chemgeo.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural environment of iron and accurate determination of Fe3+/ΣFe ratios in andesitic glasses by XANES and Mössbauer spectroscopy

Abstract: 11Andesitic glasses equilibrated at 1350 °C over a range of oxygen fugacities 12 (log fO 2 from -8.63 to -0.68) were examined with Fe K-edge X-ray absorption 13 near-edge structure (XANES) and Mössbauer spectra. XANES spectral features 14 were then calibrated as a function of Mössbauer-derived Fe 3+ /∑Fe ratios. 15Additionally, both methods help characterize the local structure of iron ions in 16 andesitic glasses. Fe 3+ /∑Fe ratios were determined from Mössbauer spectra 17 collected at room temperature but co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…Experimental durations were 6 hours for 1400ºC experiments following previous work (Stanley et al 2014;Armstrong et al 2015), and 4 hours for 1600ºC experiments. Experiments were quenched at rates of ~125°C/s for BaCO 3 and 175 °C/s for CaF 2 cells, respectively (Zhang et al, 2016), by cutting power to the furnace. Recovered capsules were mounted in ethyl-2-cyanoacrylate ("superglue") and polished for electron microprobe analysis (EPMA).…”
Section: Experimental and Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental durations were 6 hours for 1400ºC experiments following previous work (Stanley et al 2014;Armstrong et al 2015), and 4 hours for 1600ºC experiments. Experiments were quenched at rates of ~125°C/s for BaCO 3 and 175 °C/s for CaF 2 cells, respectively (Zhang et al, 2016), by cutting power to the furnace. Recovered capsules were mounted in ethyl-2-cyanoacrylate ("superglue") and polished for electron microprobe analysis (EPMA).…”
Section: Experimental and Analytical Techniquesmentioning
confidence: 99%
“…and the resulting f O2 calculated from equations (3) and (4) was compared to the IW buffer determined following Zhang et al (2016).…”
Section: Oxygen Fugacity Calculationsmentioning
confidence: 99%
“…It has been shown that the centroid of the pre-edge feature in Fe K-edge XANES spectra can be used as a quantitative measure of oxidation state (Berry et al, 2003;Cottrell and Kelley, 2011;Cottrell et al, 2009;Knipping et al, 2015;Wilke et al, 2007;Wilke et al, 2005;Zhang et al, 2016). Such quantification typically relies upon calibration to a series of glasses of varying and known (by other means) Fe 3+ /ΣFe, but otherwise fixed composition, and has been shown to depend somewhat on the bulk composition.…”
Section: Oxidation State Of Ironmentioning
confidence: 99%
“…Additional information on these issues can be expected particularly from X‐ray absorption spectroscopy (XAS) at the Fe K ‐edge. This method has been extensively applied to many different crystalline and amorphous materials and has been proven to be extremely valuable . X‐ray absorption near‐edge structure (XANES) at the Fe K ‐edge, in particular the pre‐edge feature, contains information about the oxidation state and the coordination number of iron in amorphous materials such as glass, while relying on the comparison with model compounds.…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray absorption near‐edge structure (XANES) at the Fe K ‐edge, in particular the pre‐edge feature, contains information about the oxidation state and the coordination number of iron in amorphous materials such as glass, while relying on the comparison with model compounds. Measurements of many different crystalline model compounds as well as calibration against Mössbauer data and wet chemical analyses have led to the establishment of reliable relationships between oxidation state/coordination number of Fe and position/intensity of the pre‐edge feature in the X‐ray absorption spectrum at the Fe K ‐edge, making these relationships a very useful tool for the interpretation of XANES spectra and the characterization of materials. In this study, three synthetic slags in the CaO–FeO x –SiO 2 system were synthesized, and various IPs were produced by mixing the ground slags with different alkali silicate solutions.…”
Section: Introductionmentioning
confidence: 99%